Ipsilateral free semitendinosus tendon graft transfer for reconstruction of chronic tears of the Achilles tendon - Gougoulias Nikolaos (BMC Musculoskeletal Disorders, 2008)
Abstract Background Many techniques have been developed for the reconstruction of the Achilles tendon in chronic tears. In presence of a large gap (greater than 6 centimetres), tendon augmentation is required. Methods We present our method of minimally invasive semitendinosus reconstruction for the Achilles tendon using one para-midline and one midline incision. Results The first incision is a 5 cm longitudinal incision, made 2 cm proximal and just medial to the palpable end of the residual tendon. The second incision is 3 cm long and is also longitudinal but is 2 cm distal and in the midline to the distal end of the tendon rupture. The distal and proximal Achilles tendon stumps are mobilised. After trying to reduce the gap of the ruptured Achilles tendon, if the gap produced is greater than 6 cm despite maximal plantar flexion of the ankle and traction on the Achilles tendon stumps, the ipsilateral semitendinosus tendon is harvested. The semitendinosus tendon is passed through small incisions in the substance of the proximal stump of the Achilles tendon, and it is sutured to the Achilles tendon. It is then passed beneath the intact skin bridge into the distal incision, and passed from medial to lateral through a transverse tenotomy in the distal stump. With the ankle in maximal plantar flexion, the semitendinosus tendon is sutured to the Achilles tendon at each entry and exit point Conclusion This minimally invasive technique allows reconstruction of the Achilles tendon using the tendon of semitendinosus preserving skin integrity over the site most prone to wound breakdown, and can be especially used to reconstruct the Achilles tendon in the presence of large gap (greater than 6 centimetres).